A homozygous R262Q mutation in the gonadotropin-releasing hormone receptor presenting as constitutional delay of growth and puberty with subsequent borderline oligospermia. - Lin, L; Conway, G; Hill, N; Dattani, M; Hindmarsh, P; Achermann, J (2006)
CONTEXT: The GnRH receptor plays a central role in regulating gonadotropin synthesis and release, and several mutations in the GNRHR gene have been reported in patients with idiopathic or familial forms of isolated hypogonadotropic hypogonadism (IHH). OBJECTIVE: The objective of the study was to investigate whether partial loss-of-function mutations in the GnRH receptor might be responsible for delayed puberty phenotypes. PATIENTS: Patients included sibling pairs with delayed puberty (n = 8) or those in whom one brother had delayed puberty and another had hypogonadotropic hypogonadism (n = 3). METHODS: Methods included mutational analysis of the GNRHR gene. RESULTS: A homozygous R262Q mutation in the GnRH receptor was identified in two brothers from one family. In this kindred, the proband presented at 15 yr of age with delayed puberty. After a short course of testosterone, he seemed to be progressing through puberty appropriately and was discharged from follow-up. His younger brother was also referred with delayed puberty but showed little progress after treatment. Frequent sampling revealed detectable but apulsatile LH and FSH release. His clinical progress was consistent with IHH, and he requires ongoing testosterone replacement. CONCLUSIONS: Homozygous partial loss-of-function mutations in the GnRH receptor, such as R262Q, can present with variable phenotypes including apparent delayed puberty. Ongoing clinical vigilance might be required when patients are discharged from follow-up, especially when there is a family history of delayed puberty or IHH because oligospermia and reduced bone mineralization can occur with time.